Pharmaceutical and Analytical Evaluation on Gandhaka Maritha Loha Bhasma (International Journal of Ayurveda and Pharma Research, 2023)
Rasasastra treatises have mentioned various methods for Loha bhasma preparation. The analysis on Bhasma is carried to show that the raw metals used for preparations lose their metallic characteristics and turn into mineral complex after processing. Physico chemical evaluation helps to ascertain the difference in chemical composition, elemental analysis and external morphology of Bhasmas. Thereby we can assure the quality and safety of Bhasma. Here Loha bhasmas was prepared with Loha, Gandhaka and Kumari swarasa thereafter its physico chemical properties are evaluated. The raw material used was 100 mesh size iron powder. It was first subjected to Sodhana and thereafter grinded with equal part of Gandhaka in Kumari swarasa and subjected to Marana under 600oC temperature with muffle furnace. From third Puta onwards amount of sulphur reduced to half subsequently. Final products were subjected to Bhasmapareeksha as per PLIM and with XRD, ICP-OES, XRF and Particle Size Analysis. XRD analysis revealed the body centered cubic lattice of raw iron powder changed into crystalline nature of alpha ferric oxides in final product. Elemental analysis shows reduction in silica and other toxic elements after Bhasmeekarana. The particle size reduction of Bhasma in micro meter was confirmed through dynamic light scattering. This data also will reveal the role of Gandhaka for quick formation of Lohabhasma.